1982
DOI: 10.1007/bf00470584
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in the differential response to ethanol, barbital and pentobarbital in rats selectively bred for ethanol sensitivity

Abstract: Two lines of rats, 'least affected' (LA) and 'most affected' (MA), had been selectively bred for their differential sensitivity to ethanol. Both males and females of the LA strain were observed to be less sensitive than their MA counterparts to the acute hypnotic and motor-impairing effects of ethanol. However, a lower ethanol metabolic rate of the MA males suggests that both CNS and metabolic factors contribute to their enhanced sensitivity to ethanol. By contrast, no differences were observed between the LA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…2). This agrees well with previous reports of a lack of differential effects with respect to barbiturate-induced narcosis and motor impairment, and the observation of a much lower rate of pentobarbital elimination from the blood of female rats (Lester et al 1977;Mayer et al 1982). No analgesia was produced by the dose of pentobarbital used in any of the animal groups (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2). This agrees well with previous reports of a lack of differential effects with respect to barbiturate-induced narcosis and motor impairment, and the observation of a much lower rate of pentobarbital elimination from the blood of female rats (Lester et al 1977;Mayer et al 1982). No analgesia was produced by the dose of pentobarbital used in any of the animal groups (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Although blood ethanol levels were not determined in this study, previous work has shown that, in preceding generations (up to F23), the differential response to ethanol stems to a large extent from differences in CNS sensitivity of these animals (Lester et al 1977;Bass and Lester 1980;Mayer et al 1982). Differences in response to ethanol can therefore be generalized to include hypothermia.…”
Section: Discussionmentioning
confidence: 87%
“…A related possibility is that levels of initial alcohol sensitivity determine the extent to which tolerance can be acquired. This idea has been tested extensively in rodent models, with studies generally finding that animals bred for low alcohol sensitivity are less susceptible to acquisition of tolerance than are animals bred for higher alcohol sensitivity (e.g., Khanna et al, 1985;Mayer et al, 1982Mayer et al, , 1983Riley & Lochry, 1977). Moreover, some evidence suggests alcohol-non-preferring rodent strains-which generally show higher alcohol sensitivity-become more sensitive to alcohol's sedative effects with repeated exposures, whereas alcohol-preferring rats become less sensitive (Kurtz et al, 1996).…”
Section: Drinking-related Changes In Alcohol Sensitivitymentioning
confidence: 99%